Keterampilan Proses Sains Peserta Didik Kelas XI SMA Negeri 9 Maros Pada Mata Pelajaran Biologi yang Dibelajarkan dengan Model Discovery Learning - Wulandari R, Wulandari R; Hala, Yusminah; Bahri, Arsad (Universitas Negeri Makassar, 2018)
Abstract. The objective of the study is to find out science process skills students on discovery learning in class XI of Senior High School 9 of Maros. This study was descriptive research. The groups chosen as the study sample are XI MIPA 1 with number of students 35 people. The research data is observation of the student’s science process skills. data analysis technique with descriptive statistics. Descriptive statistics are used to describe students' science process skills. The results showed that the average increase in students' science process skills at the first meeting was 66.50%, increasing to 75.07% at the second meeting, and increasing to 81.11% at the third meeting. and is in the category of sufficient to good category. The conclusion of this research is the science process skills of grade XI MIPA 1 of SMAN 9 Maros can be improving through based discovery learning. Keywords: discovery learning, science process skills